The Errand Boy; Or, How Phil Brent Won Success - Alger, Horatio, Jr., 1832-1899 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Errand Boy; Or, How Phil Brent Won Success" by Horatio Alger, Jr. is a novel written in the late 19th century. The story centers around Phil Brent, a young boy who faces challenges and adversities after discovering that his stepmother doesn$1 (Bt consider him her son, which shakes the foundation of his identity and home life. The narrative unfolds as Phil resolves to leave his unhappy home and seek his fortune in New York City, revealing themes of resilience, ambition, and personal growth. At the start of the tale, Phil endures a painful scuffle with his stepbrother Jonas, followed by a confrontation with his stepmother, Mrs. Brent, where he learns that she does not view him as a true member of the family. This revelation prompts Phil to consider a future for himself outside of the oppressive environment he$1 (Bs lived in. He decides to leave home, sells some of his possessions to save money, and embarks on a journey to New York, where he hopes to find work and establish his independence. Along the way, he encounters various characters, such as Mr. Lionel Lake and Mr. Oliver Carter, who play crucial roles in shaping his fortunes and experiences in the big city. The opening chapters set up Phil's character as determined and resourceful, as well as foreshadowing the trials and opportunities he will face in his quest for a better life. (This is an automatically generated summary.)s
The errand boy -- Fred Sargent's revenge -- The smuggler's trap.
Release date is 2006-03-15
Produced by Mike Lough and David Widger
Keywords: Orphans -- Juvenile fiction; Conduct of life -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Inheritance and succession -- Juvenile fiction; Youth -- Conduct of life -- Juvenile fiction; Diligence -- Juvenile fiction; Success -- Juvenile fiction; Self-reliance -- Juvenile fiction; Stepmothers -- Juvenile fiction; New York (N.Y.) -- History -- 1865-1898 -- Juvenile fiction; Street life -- Juvenile fiction; Impostors and imposture -- Juvenile fiction